Porous polysaccharide scaffolds: Proof of concept study on wound healing and stem cell differentiation. (March 2022) - Gopalakrishnan Usha, Preethi; Jalajakumari, Sreekutty; Babukuttan Sheela, Unnikrishnan; Mohan, Deepa; Meena Gopalakrishnan, Archana; Sreeranganathan, Maya; Kuttan Pillai, Raveendran; Berry, Catherine; Maiti, Kaustabh Kumar; Therakathinal Thankappan, Sreelekha
The combination of desirable polymer properties and methods for synthesis, utilizing materials with various architectures, could be adopted for diverse clinical applications such as wound healing as well as stem cell differentiation. Natural polymers, particularly polysaccharides, are biocompatible and are reported to have structural similarities with extracellular matrix components. In this scenario, the present study fabricated a porous scaffold using a polysaccharide, galactoxyloglucan, isolated from Tamarind seed kernel, and studied its applications in stem cell attachment and wound healing. In-growth of human mesenchymal stem cells (hMSCs) presented a rounded morphology with increased proliferation. Scaffolds were surface-functionalized with silver nanoparticles to increase the antibacterial activity and the wound healing potential evaluated in preclinical mouse models. The current study provides an insight into how stem cells attach and grow in a naturally derived low-cost polysaccharide scaffold with antibacterial, biocompatible, and biodegradable properties.